2005
DOI: 10.1089/ten.2005.11.41
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of Proliferation and Differentiation of Human Bone Marrow Stromal Cells by Fibroblast Growth Factor 2: Potential Implications for Tissue Engineering of Tendons and Ligaments

Abstract: Bone marrow stromal cells (BMSCs) play a central role in the repair and regeneration of mesenchymal tissues. For tissue engineering of ligaments and tendons, both stimulation of cell proliferation and differentiation with increased expression of essential extracellular matrix proteins and cytoskeletal elements are desirable. This study analyzes the effect of low-dose (3 ng/mL) fibroblast growth factor 2 (FGF-2) and high-dose FGF-2 (30 ng/mL) on proliferation (bromodeoxyuridine content, spectrophotometry), diff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
131
2
1

Year Published

2006
2006
2020
2020

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 199 publications
(143 citation statements)
references
References 35 publications
9
131
2
1
Order By: Relevance
“…The medium was changed every 3 days. In a previous study with the same culture media, 23 the fibroblast nature of these cells has been demonstrated using antibodies for collagen I and III and by the up-regulation of tenascin-C. Fibroblast colonies were Giemsa stained and counted using an …”
Section: Bone Marrow Analysismentioning
confidence: 99%
“…The medium was changed every 3 days. In a previous study with the same culture media, 23 the fibroblast nature of these cells has been demonstrated using antibodies for collagen I and III and by the up-regulation of tenascin-C. Fibroblast colonies were Giemsa stained and counted using an …”
Section: Bone Marrow Analysismentioning
confidence: 99%
“…JuncosaMelvin et al further showed that mechanical stimulation of MSCs-collagen sponges constructs significantly improved tendon repair in rabbit model (Juncosa-Melvin et al 2006). In vitro, MSCs have been successfully induced into tenocytes by exposure to growth factors BMP-12 (Violini et al 2009) or low-dose FGF-2 (Hankemeier et al 2005). Meanwhile, GDF-5 has also been reported to increase mRNA expression of Col I and SCX in MSCs which are believed to be the markers of tendon/ligament differentiation (Farng et al 2008).…”
Section: Introductionmentioning
confidence: 99%
“…(Yao L et al 2006) (Cao D et al 2006) Anyway the use of tenocytes have some drawbacks such as limited availability of donor sites for cell harvest, the requirement for lengthy in vitro culture to expand the number of cells, and donor-site morbidity limit the practicality of this technique. (Hankemeier S et al 2005) (Awad HA et al 2000) Stem cells may represent the ideal source for tendon engineering.There are 2 types of stem cells: embryonic stem cells and adult stem cells, embryonic cells are totipotent, but their practical use may be limited because of ethical issues and concerns regarding cell regulation. Adult stem cells, also known as mesenchymal stem cells, show excellent regenerative capacity, the ability to proliferate rapidly in culture, and the ability to differentiate into a wide variety of cell types.…”
Section: Cellsmentioning
confidence: 99%
“…(Hankemeier S et al 2005) ) (Abrahamsson SO et al 1991) (Rickert M et al 2001) (Wang XT 2004) (Hsu C & Chang J 2004). The results of in vitro studies have shown that growth factors can promote cell proliferation and protein synthesis (Fu SC et al 2003) (Jann HW et all 1999)Injured tendons treated with growth factors show improved mechanical properties.…”
Section: Local Delivery Of Growth Factors and Gene Therapymentioning
confidence: 99%